2018
DOI: 10.1111/jgs.15412
|View full text |Cite
|
Sign up to set email alerts
|

Using Base Rate of Low Scores to Identify Progression from Amnestic Mild Cognitive Impairment to Alzheimer's Disease

Abstract: Considering normal variability in cognitive test performance when diagnosing MCI may help identify individuals at greatest risk of progression to AD with greater certainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…Not surprisingly, our results are in line with those reported by Mitchell and Shiri-Feshki (2009), who found that amnestic MCI and mdMCI had a similar risk-AD (11.7% vs. 12.2%), both having a higher risk-AD compared to naMCI. One possible explanation is that severity of memory impairments, and not the number of tests, is related to the risk-AD, as has been suggested recently (Oltra-Cucarella et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Not surprisingly, our results are in line with those reported by Mitchell and Shiri-Feshki (2009), who found that amnestic MCI and mdMCI had a similar risk-AD (11.7% vs. 12.2%), both having a higher risk-AD compared to naMCI. One possible explanation is that severity of memory impairments, and not the number of tests, is related to the risk-AD, as has been suggested recently (Oltra-Cucarella et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…A review by Binder et al (2009) showed that the probability of obtaining one or more low scores increased as the number of measures increased, with a percentage of up to 59% of participants having at least one score 1.5 standard deviations below the mean. Recently, Oltra-Cucarella et al (2018) reported that up to 90% of a sample of 280 individuals with normal cognition had up to two scores at least 1.5 standard deviations below the mean in a battery with 9 measures. These data suggest that increasing the number of tests in the neuropsychological battery increases the probability of false positive MCI cases, and also the probability of falsely being classified as having multiple-domain MCI if only two measures suffice for diagnosis in batteries with several measures.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the original ADNI MCI criteria used education-adjusted scores of WMS story recall, but scores adjusted for both age and education are likely to further improve MCI diagnosis. One study of ADNI participants categorized individuals with MCI based on the number of impaired tests and found that this criterion worked better than the original ADNI MCI classification or the Jak/Bondi actuarial approach in predicting progression from MCI to AD (Oltra-Cucarella et al 2018). This study used the average number of low scores in the worst performing 10% of ADNI CN participants as the basis for diagnosing MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 9 scores from 6 tests, the lowest 10% of CN participants had ≥3 low scores. The highest progression rate (43%) to AD in a 3year period was in those with single domain amnestic MCI (i.e., individuals who were ≥ 1.5 SD below the mean in Logical Memory delayed recall, AVLT delayed recall and AVLT recognition) (Oltra-Cucarella et al 2018). This rate was higher than the progression rate of 33% for multiple-domain amnestic MCI, probably because one could meet criteria for multiple-domain amnestic MCI with only one or two impaired memory scores but a single-domain diagnosis would require impairment on all three.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work from Bondi and Jak in longitudinal aging cohorts rather consistently demonstrates that actuarial approaches that classify cognitive impairment using patterns and frequencies of low scores have led to modest rates of clinical reversion (mild cognitive impairment or "MCI" to "cognitively normal" at follow-up), improved characterization of risk of progression to dementia, and stronger associations with biologic disease markers than "single-test" methods Bondi & Smith, 2014;Jak et al, 2009;Jak et al, 2016;Petersen et al, 1999). Oltra-Cucarella et al (2018) recently showed that the number of low scores in a test battery predicted progression from MCI to dementia in the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort with improved specificity (Oltra-Cucarella et al, 2018). Put simply, implementing these approaches increases a clinician's confidence about whether a patient's test scores reflect true cognitive changes versus normal performance variability unrelated to suspected underlying disease.…”
Section: Introductionmentioning
confidence: 99%